Physicochemical Properties and Cryoprotective Action of Solutions of Polyvinyl Alcohol, Glycerol and Media Based on Their Combinations During Freezing of Red Blood Cells - Hvozdiuk, Yana; Chekanova, Valentina; Pakhomova, Yulia; Kompaniets, Antonina (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 288